(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the linguistic and pragmatic characteristics of substantive word combinations (noun units) in the Uzbek language. The study examines their syntactic structure, semantic richness, and communicative functions in speech. The results show that substantive combinations not only serve to identify objects and phenomena, but also perform reference, evaluation, and emphasis functions in the text. This article is of scientific importance for linguistics, discourse analysis, and pragmatic research.